Boosting Solid‐State Diffusivity and Conductivity in Lithium Superionic Argyrodites by Halide Substitution. Issue 26 (24th May 2019) - Adeli, Parvin; Bazak, J. David; Park, Kern Ho; Kochetkov, Ivan; Huq, Ashfia; Goward, Gillian R.; Nazar, Linda F.
Abstract: Developing high‐performance all‐solid‐state batteries is contingent on finding solid electrolyte materials with high ionic conductivity and ductility. Here we report new halide‐rich solid solution phases in the argyrodite Li6 PS5 Cl family, Li6− x PS5− x Cl1+ x, and combine electrochemical impedance spectroscopy, neutron diffraction, and 7 Li NMR MAS and PFG spectroscopy to show that increasing the Cl − /S 2− ratio has a systematic, and remarkable impact on Li‐ion diffusivity in the lattice. The phase at the limit of the solid solution regime, Li5.5 PS4.5 Cl1.5, exhibits a cold‐pressed conductivity of 9.4±0.1 mS cm −1 at 298 K (and 12.0±0.2 mS cm −1 on sintering)—almost four‐fold greater than Li6 PS5 Cl under identical processing conditions and comparable to metastable superionic Li7 P3 S11 . Weakened interactions between the mobile Li‐ions and surrounding framework anions incurred by substitution of divalent S 2− for monovalent Cl − play a major role in enhancing Li + ‐ion diffusivity, along with increased site disorder and a higher lithium vacancy population. Abstract : At the limit of the solid solution regime : Li5.5 PS4.5 Cl1.5 exhibits a high Li + ion conductivity of 9.4 mS cm −1 at 298 K with an activation energy of 0.29 eV, and a high Li + diffusion coefficient of 1.01×10 −11 m 2 s −1 determined by NMR transport measurements, suggesting its excellent prospect as a solid Li‐ion electrolyte.